Differentiation of Impaired From Preserved Hemodynamics in Patients With Fontan Circulation Using Real-time Phase-velocity Cardiovascular Magnetic Resonance. Issue 3 (May 2017) - Körperich, Hermann; Müller, Katja; Barth, Peter; Gieseke, Jürgen; Haas, Nikolaus; Schulze-Neick, Ingram; Burchert, Wolfgang; Kececioglu, Deniz; Laser, Kai T.
Abstract : Purpose: Progressive impairment of hemodynamics in patients with Fontan circulation is common, multifactorial, and associated with decreased quality of life and increased morbidity. We sought to assess hemodynamic differences between patients with preserved (preserved Fontans) and those with impaired circulation (impaired Fontans) after pulmonary vasodilation using oxygen and under forced breathing conditions. Materials and Methods: Real-time phase-contrast cardiovascular magnetic resonance was performed using non–ECG triggered echo-planar imaging (temporal resolution=24 to 28 ms) in the ascending aorta (AAo) and superior vena cava (SVC)/inferior vena cava (IVC) on room air, after 100% oxygen inhalation (4 L/min; 10 min) and on forced breathing in 29 Fontan patients (17.2±7.3 y) and in 32 controls on room air (13.4±3.7 y). The simultaneously recorded patients' respiratory cycle was divided into 4 segments (expiration, end-expiration, inspiration, and end-inspiration) to generate respiratory-dependent stroke volumes (SVs). The imaging data were matched with physiological data and analyzed with home-made software. Results: The mean SVi (AAo) was 46.1±11.1 mL/m 2 in preserved Fontans versus 30.4±6.2 mL/m 2 in impaired Fontans ( P =0.002) and 51.1±6.9 mL/m 2 in controls ( P =0.107). The cutoff value for differentiation of Fontan groups was SVi (AAo, end-expiratory) of 32.1 mL/m 2 . After hyperoxygenation, the mean SVi (AAo) increased to 48.7±12.7 mL/m 2 in preserved Fontans ( P =0.045) but remained unchanged in impaired Fontans (31.1±5.8 mL/m 2, P =0.665). Simultaneously, heart rates decreased from 75.2±15.9 to 70.8±16.4 bpm (preserved; P =0.000) but remained unchanged in impaired circulation (baseline: 84.1±9.8 bpm, P =0.612). Compared with physiological respiration, forced breathing increased the maximum respiratory-related cardiac index difference (ΔCImax ) in preserved Fontans (SVC: 2.5-fold, P =0.000; and IVC: 1.8-fold, P =0.000) and to a lower extent in impaired Fontans (both veins, 1.5-fold; P(SVC)=0.011, P(IVC)=0.013). There was no impact on mean blood flow. Conclusions: Oxygen affected the pulmonary vascular system by vasodilation and increased SVi in preserved Fontans but had no effect on impaired Fontans. Forced breathing increased ΔCImax but did not change the mean blood flow by sole activation of the ventilatory pump. End-expiratory aortic SVi represents a valuable measure for classifying the severity of Fontan hemodynamics impairment. Abstract : Supplemental Digital Content is available in the text.